2010
DOI: 10.1253/circj.cj-09-0705
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Plaque Regression and Lifestyle Modification in Patients Treated With Pravastatin - Assessment Mainly by Daily Aerobic Exercise and an Increase in the Serum Level of High-Density Lipoprotein Cholesterol -

Abstract: Background:The purpose of this study was to explore the effect of lifestyle modification, mainly daily aerobic exercise, on coronary atherosclerosis in patients with coronary artery disease (CAD). Methods and Results:A 6-month prospective observational study was conducted with 84 CAD patients receiving pravastatin treatment in order to evaluate the relationship between lifestyle modification, in particular aerobic exercise, and plaque volume as assessed by intravascular ultrasound (IVUS). Lifestyle during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…This latter observation may explain certain effects of treatments on atherosclerotic plaques, in particular, the observation that plaque regression can occur when the treatments augments the HDL-C levels [2]. Our previous studies and other studies have also shown that an increase in the serum HDL-C level is an independent predictor of coronary plaque regression [6,10].…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…This latter observation may explain certain effects of treatments on atherosclerotic plaques, in particular, the observation that plaque regression can occur when the treatments augments the HDL-C levels [2]. Our previous studies and other studies have also shown that an increase in the serum HDL-C level is an independent predictor of coronary plaque regression [6,10].…”
Section: Discussionmentioning
confidence: 58%
“…We have previously reported that a decreased peripheral monocyte count and elevated serum HDL-C level are independently involved in the effect of statins in promoting regression of coronary plaques [5,6]. As described before, monocytes and HDL-C have apparently opposing functions in the progression or inhibition of atherosclerosis.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Lifestyle modification was assessed by a questionnaire with special focus on daily exercise, weight management, and smoking status. Multivariate regression analysis revealed that lifestyle modification independently predicted plaque regression, leading the authors to conclude that increased physical activity may play an important role 98. However, the change in physical activity over time was not reported and not correlated with plaque regression, independent of other lifestyle factors.…”
Section: Mechanism 3: Regression Of Coronary Stenosismentioning
confidence: 98%
“…However, Tani et al reported that successful life style modification with exercise, body weight reduction and smoking cessation for 6 months was associated with coronary plaque volume regression in low prognostic risk CAD patients. 34 Belardinelli et al reported in the ETICA (Exercise Training Intervention after Coronary Angioplasty) trial that a 6-month OPCR for the relatively low risk CAD patients after successful PCI (49% having AMI) reduced cardiac events and hospital re-admission during the follow-up period (33±7 months). 35 In addition, because the magnitude of the improvement in endothelial function afforded by OPCR does not correlate with the improvements in CRF, 36 the general consensus at present is that the favorable effect of OPCR on the long-term prognosis is mediated by a direct anti-atherosclerosis effect of exercise training rather than by improvements in CRF.…”
Section: Discussionmentioning
confidence: 99%